Depression and unemployment incidence rate evolution in Portugal, 1995-2013: General Practitioner Sentinel Network data - Ana Paula Rodrigues; Mafalda Sousa-Uva; Rita Fonseca; Sara Marques; Nuno Pina; Carlos Matias-Dias (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Quantify, for both genders, the correlation between the depression incidence rate and the unemployment rate in Portugal between 1995 and 2013. METHODS An ecological study was developed to correlate the evolution of the depression incidence rates estimated by the General Practitioner Sentinel Network and the annual unemployment rates provided by the National Statistical Institute in official publications. RESULTS There was a positive correlation between the depression incidence rate and the unemployment rate in Portugal, which was significant only for males (R2 = 0.83, p = 0.04). For this gender, an increase of 37 new cases of depression per 100,000 inhabitants was estimated for each 1% increase in the unemployment rate between 1995 and 2013. CONCLUSIONS Although the study design does not allow the establishment of a causal association between unemployment and depression, the results suggest that the evolution of unemployment in Portugal may have had a significant impact on the level of mental health of the Portuguese, especially among men.